A trainer’s guide for participatory learning and action (Sustainable Agriculture Programme, 1995)
Chapter headings include: -Adult Learning -You, The Trainer and Facilitator -Group Dynamics and Team Building -Principles of Participatory Learning and Action -Training in Participatory Methods in the Workshop -The challenges of Training in the Field -Organizing workshops for Training, (Orientation and Exposure) -Plus: 101 games and Exercises for Trainers